2020
DOI: 10.3390/ma13204617
|View full text |Cite
|
Sign up to set email alerts
|

Frost Damage in Tight Sandstone: Experimental Evaluation and Interpretation of Damage Mechanisms

Abstract: Low-porosity tight rocks are widely used as building and engineering materials. The freeze–thaw cycle is a common weathering effect that damages building materials in cold climates. Tight rocks are generally supposed to be highly frost-resistant; thus, studies on frost damage in tight sandstone are rare. In this study, we investigated the deterioration in mechanical properties and changes in P-wave velocity with freeze–thaw cycles in a tight sandstone. We also studied changes to its pore structure using nuclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…In fact, surrounding rock suffers freeze-thaw cycles and deteriorates during the operation stage of cold region tunnels. Ding et al (2020) investigated the deterioration in mechanical properties with freeze-thaw cycles in a tight sandstone and studied changes to its pore structure using nuclear magnetic resonance technology. Huang et al (2022a, b) studied the pore structure change of red sandstone under freeze-thaw cycles by mercury intrusion porosimetry and found that both the uniaxial compressive strength and the triaxial compressive strength decrease due to the growth of macropores.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, surrounding rock suffers freeze-thaw cycles and deteriorates during the operation stage of cold region tunnels. Ding et al (2020) investigated the deterioration in mechanical properties with freeze-thaw cycles in a tight sandstone and studied changes to its pore structure using nuclear magnetic resonance technology. Huang et al (2022a, b) studied the pore structure change of red sandstone under freeze-thaw cycles by mercury intrusion porosimetry and found that both the uniaxial compressive strength and the triaxial compressive strength decrease due to the growth of macropores.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the study of rock mechanics in cold regions has gradually become one of the hot topics, and the application of new technologies and means promotes its development, such as Nuclear Magnetic Resonance (NMR) technology (Ding et al 2020;Zhou et al 2015;Liu et al 2021;Jia et al 2020;Liu et al 2020a;Pan et al 2020;Zhang et al 2020d;Liu et al 2020b;), Ultrasonic Detections (Ding et al 2020;Wang et al 2017;Çelik, 2020;Wang et al 2019;Ivankina et al 2020), Digital Image Correlation (DIC) (Mardoukhi et al 2021), Neutron Diffraction Measurements (Ivankina et al 2020), Scanning Electron Microscope (SEM) (Wang et al 2017;Çelik, 2020;Wang et al 2019;Chang et al 2020;Abdolghanizadeh et al 2020;Fang et al 2018;Zhou et al 2018;Yang et al 2021b;Zhou et al 2019;Zhao et al 2019), Computed Tomography (CT) technique (Wang et al 2020b), Optical Microscope (Çelik, 2020;Mousavi et al 2020), X-ray Computed Micro-tomography (Deprez et al 2020b), X-ray diffraction (XRD) (Zhao et al 2019;Mousavi et al 2020), Acoustic Emission (Wang et al 2020b;Xiao et al 2020), Infrared thermography (Yang et al 2021a). These new techniques and their combined applications help to discover new features in experiments and provide verification means for the development of theory or numerical simulation.…”
Section: Introductionmentioning
confidence: 99%
“…In Europe, on the other hand, several examples on characterization of physical and mechanical characteristics of construction materials can be mentioned: dry stone heritage materials and limestone from Portugal [ 19 , 20 ], freshwater limestones used in Bosnia and Herzegovina [ 21 ] and limestones from Italy [ 22 ]. Techniques involve on-site testing [ 23 ] and adoption of non-destruction techniques [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%